A systematic review of orthopaedic manual therapy randomized clinical trials quality. (19th October 2016) - Riley, Sean P.; Swanson, Brian; Brismée, Jean-Michel; Sawyer, Steven F.
Abstract : Study Design : Systematic review and meta-analysis. Objectives : To conduct a systematic review and meta-analysis of randomized clinical trials (RCTs) in the orthopaedic manual therapy (OMT) literature from January 2010 to June 2014 in order to determine if the CONSORT checklist and Cochrane Risk of Bias (RoB) assessment tools: (1) are reliable; (2) have improved the reporting and decreased the risk of bias in RCTs in the OMT literature; (3) differ based on journal impact factor (JIF); and (4) scores are associated with each other. Background : The CONSORT statement is used to improve the accuracy of reporting within RCTs. The Cochrane RoB tool was designed to assess the risk of bias within RCTs. To date, no evaluation of the quality of reporting and risk of bias in OMT RCTs has been published. Methods : Relevant RCTs were identified by a literature review from January 2010 to June 2014. The identified RCTs were assessed by two individual reviewers utilizing the 2010 CONSORT checklist and the RoB tool. Agreement and a mean composite total score for each tool were attained in order to determine if the CONSORT and RoB tools were reliable and varied by year and impact factor. Results : A total of 72 RCTs in the OMT literature were identified. A number of categories within the CONSORT and RoB tools demonstrated prevalence-adjusted bias-adjusted kappa (PABAK) scores of less than 0.20 and from 0.20 to 0.40. The total CONSORT and RoB scores were correlated to each other ( r = 0.73; 95% CI 0.60 to 0.82; p < 0.0001). There were no statistically significant differences in CONSORT or RoB scores by year. There was a statistically significant correlation between both CONSORT scores and JIF ( r = 0.64, 95% CI 0.47 to 0.76; p < 0.0001), and between RoB scores and JIF ( r = 0.42, 95% confidence interval 0.21–0.60; p < 0.001). There was not a statistically significant correlation between JIF and year of publication. Conclusion : Our findings suggest that the CONSORT and RoB have a number of items that are unclear and unreliable, and that the quality of reporting in OMT trials has not improved in recent years. Improvements in reporting are necessary to allow advances in OMT practice. Level of Evidence : 1A